(untitled) (Global Journal of Human-Social Science, 2019)
In the 20 th as well as in the 21 st century, it has already been witnessed by human beings that the earth is going to encounter environmental change, and this change is directing us to a disastrous future. All the branches of human knowledge are concerned about this. In this respect, literature is not silent and plays a significant role. Ecocriticism analyses the representation of nature in literature, it traces the process of environmental disruption and comments on the overall situation for a solution. In this research article, R K Narayan’s novel The Man-eater of Malgudi is seen from an ecocritical perspective. This article considers the issue of abusing animals by Vasu, the most enigmatic character in the novel, and shows how different characters react in different ways about this abuse. As it is related to environment, probable suggestion for saving the environment is expected. This article also highlights this issue.